Solving the Equation: (x + 2)(x  9) = 0
This equation represents a quadratic expression in factored form. To solve for the values of x that satisfy the equation, we can use the Zero Product Property.
Zero Product Property
The Zero Product Property states that if the product of two or more factors is equal to zero, then at least one of the factors must be equal to zero.
Applying the Property
In our equation, we have two factors: (x + 2) and (x  9). Therefore, for the product to be equal to zero, either:

(x + 2) = 0
Solving for x, we get: x = 2 
(x  9) = 0 Solving for x, we get: x = 9
Conclusion
Therefore, the solutions to the equation (x + 2)(x  9) = 0 are x = 2 and x = 9.
This means that if you substitute either 2 or 9 for x in the original equation, the equation will hold true.